The Missing Scholarship Behind Virtual Heritage Infrastructures - Champion, Erik (2016)
This theoretical position paper outlines four key issues blocking the development of effective 3D models that would be suitable for the aims and objectives of virtual heritage infrastructures. It suggests that a real-time game environment which composes levels at runtime from streaming multimédia components would offer advantages in terms of editing, customisation and personalisation. The paper concludes with three recommendations for virtual heritage infrastructures.